DYNAMICS OF MOTIVATION FEATURES TO PHYSICAL CULTURE AMONG STUDENTS OF NON-SPORTS SPECIALTIES - Gut, Yu.N.; Kabardov, M.K.; Kosheleva, Yu.P.; Zhambeeva, Z.Z.; Osnitsky, A.K. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the dynamics of the peculiarities of motivation for physical education of students-psychologists in the process of studying at the university. Methods and structure of the study. The experiment was carried out with the participation of students of the Faculty of Psychology of the National Research University "BelSU" in two stages: in 2019 at the 1st year and in 2022 at the 4th year among undergraduate students. In total, 98 1st year students took part in the study in 2019 and 97 4th year undergraduate students in 2022. The main methods were: the method of diagnosing a personality for motivation for success and avoiding failures by T. Ehlers, the method "Motives for playing sports" by A.V. Shaboltas, as well as the questionnaire "Attitude towards physical culture". Results and conclusions. The dynamics of differences in the motives that encourage students to engage in physical culture from the first to the fourth year have been revealed. It was found that students in the first year were more often and more actively engaged in physical activity, but by the senior year they have a more conscious opinion that regular physical education improves health and improves mood. The results of the study can be used when conducting physical education classes for first-year students of non-sports specialties in order to optimize the problem of developing the motivation to preserve and improve health in the process of studying at a university and after graduation.